2012
DOI: 10.1002/jbm.a.34007
|View full text |Cite
|
Sign up to set email alerts
|

High thrombin concentrations in fibrin sealants induce apoptosis in human keratinocytes

Abstract: Over the last century many studies have been performed to assess the impact of fibrin sealant (FS) components on cells. Because of the noncovalent bonding of thrombin to fibrin during fibrin clot formation, we wanted to further evaluate the impact of fibrin bound thrombin on cell viability. Initially, we quantified the activity of thrombin in three different, commercially available FS. This information was used to prepare fibrin clots covering a range of thrombin concentrations from 4 to 820 IU mL(-1), but whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 47 publications
2
11
0
3
Order By: Relevance
“…They concluded that the most favorable combination for survival of bone marrow stromal cells was 20 mg/mL of fibrinogen and 87 NIH units/mL of thrombin, values intermediate between those of our control and low-low groups. The ratio of dead to total cells in our study was <30%, a finding consistent with previous reports 18,27 . Gugerell et al reported that thrombin concentrations of >400 NIH units/mL induced apoptosis of human keratinocytes 27 .…”
Section: Effect O F Fibrin F O R M U L At I O N O N T E N D O N R E Psupporting
confidence: 93%
See 2 more Smart Citations
“…They concluded that the most favorable combination for survival of bone marrow stromal cells was 20 mg/mL of fibrinogen and 87 NIH units/mL of thrombin, values intermediate between those of our control and low-low groups. The ratio of dead to total cells in our study was <30%, a finding consistent with previous reports 18,27 . Gugerell et al reported that thrombin concentrations of >400 NIH units/mL induced apoptosis of human keratinocytes 27 .…”
Section: Effect O F Fibrin F O R M U L At I O N O N T E N D O N R E Psupporting
confidence: 93%
“…The ratio of dead to total cells in our study was <30%, a finding consistent with previous reports 18,27 . Gugerell et al reported that thrombin concentrations of >400 NIH units/mL induced apoptosis of human keratinocytes 27 . Given our findings, we agree with Gugerell et al that much lower thrombin concentrations are appropriate for fibrin gels used for cell delivery.…”
Section: Effect O F Fibrin F O R M U L At I O N O N T E N D O N R E Psupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast to other approaches using rather low fibrinogen to thrombin ratios [10,11,34,39], we chose a higher ratio (20 mg/mL fibrinogen, 0.625 U/mL thrombin) in our experimental setup for several reasons: (i) the stiffness is directly proportional to the fibrinogen concentration. The obtained constructs displayed a Young's modulus of about 17 kPa, which lies within the stiffness range proposed to be most suitable for myogenic differentiation [43,47,73]; (ii) the fibrinogen to thrombin ratio directly correlates with permeability and pore size as well as the ultimate tensile strength of the scaffold [16]; (iii) lower thrombin concentrations give slower clotting times, increasing the homogeneity of the fibrin meshwork, and have less detrimental effects on cell viability [74].…”
Section: Discussionmentioning
confidence: 99%
“…Gugerell et al reported that high concentrations (about 820 U/mL) of thrombin activated apoptotic mechanisms in keratinocytes, and also decreased their attachment and spreading on fibrin sealants. 45 Kubo et al showed that fibrin and fibrinogen were nonadhesive for keratinocytes, due to a lack in these cells of α v β 3 integrin receptors, which are important for binding cells to fibrin molecules. 46 In our study, the HaCaT keratinocytes were able to adhere to fibrin-coated membranes, though they were not so well flattened as on collagen-coated membranes.…”
Section: Figure 11mentioning
confidence: 99%